Authoritarian Environmentalism and Sustainable Development Explaining China's Ecological Civilization Success and Its Structural Limits for the Post-Colonial Global South - Arif Darmawan; Elpeni Fitrah; Renny Miryanti; Soni Martin Anwar; Kiky Srirejeki; Aryuni Yuliantiningsih; Ulil Afwa; Hanifa Pascarina (Institute of International Studies, 2025)
In response to the escalating global environmental crisis, China has initiated